Key Regulatory Differentially Expressed Genes in the Blood of Atrial Septal Defect Children Treated With Occlusion Devices - Li, Bo-Ning; Tang, Quan-Dong; Tan, Yan-Lian; Yan, Liang; Sun, Ling; Guo, Wei-Bing; Qian, Ming-Yang; Chen, Allen; Luo, Ying-Jun; Zheng, Zhou-Xia; Zhang, Zhi-Wei; Jia, Hong-Ling; et al. (Frontiers in Genetics, 2021)
Atrial septal defects (ASDs) is the most common types of cardiac septal defects in congenital heart defects. In addition to traditional therapy, interventional closure has become the main treatment methods. However, the molecular events and mechanisms underlying the repair progress by occlusion device remain unknown. In this study, we aimed to characterize differentially expressed genes (DEGs) in the blood of patients treated with occlusion devices (metal or poly-L-lactic acid devices) using RNA-sequencing, and further validated them by qRT-PCR analysis to finally determine the expression of key mediating genes after closure of ASD treatment. The result showed that total 1045 genes and 1523 genes were expressed differently with significance in metal and poly-L-lactic acid devices treatment, respectively. The 115 overlap genes from the different sub-analyses are illustrated. The similarities and differences in gene expression reflect that the body response process involved after interventional therapy for ASDs has both different parts that do not overlap and the same part that crosses. The same portion of body response regulatory genes are key regulatory genes expressed in the blood of patients with ASDs treated with closure devices. The gene ontology enrichment analysis showed that biological processes affected in metal devices therapy are immunity response with CXCR4 genes and poly-L-lactic acid devices treatment key pathway is nuclear-transcribed mRNA catabolic process and proteins targeting to endoplasmic reticulum process with ribosomal proteins (such as RPS26). We confirmed CXCR4, TOB1 and DDIT4 gene expression are both significantly down regulated toward the pre-therapy level after the post treatment in both therapy groups by qRT-PCR. Our study suggests the potential role of CXCR4, DDIT4 and TOB1 may be key regulatory genes in the process of endothelialization in the repair progress of ASDs, providing molecular insights in this progress for the future study.